2021
DOI: 10.3390/foods10061406
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antimicrobial Activities of Combinations of Vanillin and Essential Oils of Cinnamon Bark, Cinnamon Leaves, and Cloves

Abstract: Plant bioactive compounds have antimicrobial and antioxidant activities that allow them to be used as a substitute for synthetic chemical additives in both food and food packaging. To improve its sensory and bactericidal effects, its use in the form of effective combinations has emerged as an interesting possibility in the food industry. In this study, the antimicrobial activities of essential oils (EOs) of cinnamon bark, cinnamon leaves, and clove and the pure compounds vanillin, eugenol, and cinnamaldehyde w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 58 publications
0
13
1
Order By: Relevance
“…To the best of our knowledge, no prior research has claimed a synergy between Origanum EOs and antibiotics on multiresistant foodborne Salmonella in Morocco. Nonetheless, the majority of research focuses on the potential medical benefits of EOs either alone or when combined (Cava‐Roda et al, 2021; Fadil et al, 2018; Tardugno et al, 2018). Indeed, it is interesting to note that efforts have been made to investigate the bioactive characteristics of EOs from various Origanum species.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no prior research has claimed a synergy between Origanum EOs and antibiotics on multiresistant foodborne Salmonella in Morocco. Nonetheless, the majority of research focuses on the potential medical benefits of EOs either alone or when combined (Cava‐Roda et al, 2021; Fadil et al, 2018; Tardugno et al, 2018). Indeed, it is interesting to note that efforts have been made to investigate the bioactive characteristics of EOs from various Origanum species.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the mechanisms of action of phenolic monoterpene compounds in EOs are mainly associated with their activity on cell viability, and their interaction with transcriptional regulators of QS communication, biofilm formation, and virulence genes has been proposed [ 75 , 76 ]. In addition, it has been evidenced that the activity of the major components of an EO could be altered by its minor components, either in a synergistic, antagonistic, or neutral way, depending on the relative amount of these minor components [ 77 , 78 ]. Therefore, the effect of an EO could vary between microorganisms and even between different strains of the same microorganism [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the heterogeneous composition of OEOs and the antimicrobial activities of many OEO components, it seems unlikely that there is only one mechanism of action or that only one component is responsible for the antimicrobial action. At the same time, the various chemical components contained in plant EOs often have synergistic effects, and the diversity of antibacterial targets can greatly reduce the resistance of bacteria [31,32].…”
Section: Antibacterial Activity Of Oeosmentioning
confidence: 99%